Permanent LMN denervation of human skeletal muscle and recovery by h-b FES: management and monitoring - Helmut Kern; Roberto Stramare; Leonora Martino; Riccardo Zanato; Paolo Gargiulo; Ugo Carraro (PAGEPress Publications, 2010)
Denervation of a defined skeletal muscle is due to lower motor neuron (LMN) or peripheral nerve lesions that have major consequences on the muscle tissue. After early atrophy, the mid- and late-phases presents two very contrasting myofibers populations: beside those severely atrophic with internalized groups of myonuclei, large fast-type muscle fibers continue to be present 4 to 6 years after Spinal Cord Injury (SCI). Recent results of rat experiments provides the rational basis for understanding the residual functional characteristics of the long-term denervated muscle and the molecular explanation of its ability to respond to home-base functional electrical stimulation (h-b FES) using custom-designed electrodes and stimulators. Further outcomes of the Vienna-Padova ten-year collaboration are: 1. a world-unique Myo- Bank of muscle biopsies and 2. improved imaging procedures (Color Computer Tomography (CT) scan and Functional Echomyography), all demonstrating that h-b FES induces improvements in muscle contractility, tissue composition and mass, despite permanent LMN denervation. The benefits of h-b FES could be extended from patents suffering with complete Conus-Cauda Syndrome to the numerous patients with incomplete LMN denervation of skeletal muscles to determine whether h-b FES reduces secondary complications related to disuse and impaired blood perfusion (reduction in bone density, risk of bone fracture, decubitus ulcers, and pulmonary thromboembolism). We are confident that translation of the results of a clinical experiment, the EU Project RISE, to the larger cohort of incomplete LMN denervated muscles will provide the wanted results.